ENGLISH TEACHERS’ STRATEGIES IN STIMULATING STUDENTS’ MOTIVATION TO LEARN ENGLISH IN CLASS X SMA NEGERI 19 BULUKUMBA - Muslim, Amanda Defasya Asyrah; Samtidar, Samtidar; Farahdiba, Syarifah (Universitas Negeri Makassar, 2025)
This study aims to examine the English Teachers’ Strategies in Students’ Motivation to Learn English. This research uses qualitative research by using two instruments, namely interviews and observations. The independent variable of this research is ‘English Teacher Strategy’ and the dependent variable of this research is ‘Students’ English Learning Motivation’. This research was conducted at SMA Negeri 19 Bulukumba, with the research subject being an English teacher who consists of only one person. This research was carried out twice a week, which consisted of conducting the first interview before making observations, then conducting observations and interviews after making observations. The data collection techniques in this study were the interview process, which was recorded later and observation, which used an observation checklist. The results of the study show that there are English teacher strategies in stimulating students' English learning motivation in class X, including Brainstorming and Using Resources for Receiving and Sending Messages. In addition, this study also explains that there are several factors that influence students' learning motivation, especially in English lessons, where English teachers must be more careful in using and applying strategies in teaching.